Basic Literacy and Attainment of Good Health and Well-Being among Young Adults in Ekiti State, Nigeria - Owolewa, Olusegun O.; Adepoju, Omolola F. (International Journal of Emerging Trends in Social Sciences, 2018)
Eradication of poverty and shifting the world onto a sustainable and resilient development pathway are part of the many agenda set at different times in history of the world by the United Nations. The realisation of these agenda is largely presumed to rest on literacy level of the world. Most health challenges in the nation have proven difficult to control or handle because the level of health literacy amongst Nigerians appears inadequate in the aspects that directly impact their health. The main purpose of this study was to establish the link between Sustainable Development Goals (SDGs) 3 and basic literacy, and determine, both quantitatively and qualitatively, how it affects the achievement of SDG 3 among young adults. A naturalistic inquiry was adopted to obtain data among the targeted population; questionnaire was formulated to answer the set research questions; 250 respondents within ages 18 to 35 were targeted, 125 each from selected LGA. Results of the study showed that basic/health literacy has significant influence on the health perception of the population. The study further shows that health performance is a function of health literacy and indirect function of level of education. This study recommended that government at all levels should embark on serious awareness campaign to intimate all Nigerians with SDGs and incorporate health programmes and awareness as a compulsory aspect of education at all levels.